Proteomic analysis of media from lung cancer cells reveals role of 14-3-3 proteins in cachexia - McLean, Julie B.; Moylan, Jennifer S.; Horrell, Erin M. W.; Andrade, Francisco H. (Frontiers in Physiology, 2015)
AIMS: At the time of diagnosis, 60% of lung cancer patients present with cachexia, a severe wasting syndrome that increases morbidity and mortality. Tumors secrete multiple factors that contribute to cachectic muscle wasting, and not all of these factors have been identified. We used Orbitrap electrospray ionization mass spectrometry to identify novel cachexia-inducing candidates in media conditioned with Lewis lung carcinoma cells (LCM). Results: One-hundred and fifty-eight proteins were confirmed in three biological replicates. Thirty-three were identified as secreted proteins, including 14-3-3 proteins, which are highly conserved adaptor proteins known to have over 200 binding partners. We confirmed the presence of extracellular 14-3-3 proteins in LCM via western blot and discovered that LCM contained less 14-3-3 content than media conditioned with C2C12 myotubes. Using a neutralizing antibody, we depleted extracellular 14-3-3 proteins in myotube culture medium, which resulted in diminished myosin content. We identified the proposed receptor for 14-3-3 proteins, CD13, in differentiated C2C12 myotubes and found that inhibiting CD13 via Bestatin also resulted in diminished myosin content. Conclusions: Our novel findings show that extracellular 14-3-3 proteins may act as previously unidentified myokines and may signal via CD13 to help maintain muscle mass.